2004
DOI: 10.5194/hess-8-436-2004
|View full text |Cite
|
Sign up to set email alerts
|

Long-term changes in precipitation and stream water chemistry in small forest and moorland catchments at Beddgelert Forest, north Wales

Abstract: Changes in the chemistry of bulk precipitation and stream water between 1982 and 2000 are described for small moorland and forest catchments located within Beddgelert Forest in north Wales. Two forest catchments were partially clearfelled in 1984 (D2; 68% and D4; 28%) whilst a third (D3) remained as an unfelled control until autumn / winter 1998/99 when partial felling took place in the headwaters. Over the monitoring period, the annual mean pH of bulk precipitation increased from 4.6 to 5.1 whilst the annual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The experimental plots were 320-350 m in altitude in a formerly glaciated valley with acid predominantly ferric stagnopodzols, formed primarily from basepoor Ordovician slates, shales or mudstone . The site has a temperate maritime climate with mean soil temperature at 30 cm depth of 8 8C and mean annual rainfall of 2800 mm (Reynolds et al, 2004). Detailed descriptions of soils, geology and climate are provided by Stevens and Hornung (1988).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The experimental plots were 320-350 m in altitude in a formerly glaciated valley with acid predominantly ferric stagnopodzols, formed primarily from basepoor Ordovician slates, shales or mudstone . The site has a temperate maritime climate with mean soil temperature at 30 cm depth of 8 8C and mean annual rainfall of 2800 mm (Reynolds et al, 2004). Detailed descriptions of soils, geology and climate are provided by Stevens and Hornung (1988).…”
Section: Site Descriptionmentioning
confidence: 99%
“…The vast majority of published work has been focussed in the Plynlimon catchments in Mid-Wales, complemented by other work in Wales at Beddgelert, Llyn Brianne, and Llanbrymair (e.g. Reynolds et al, 1989Reynolds et al, , 1992Neal et al, 1992;Soulsby, 1995;Hudson et al, 1997;Reynolds et al, 2004). In Scotland, where much of the UK's commercial forestry has been planted, experimental catchments have been established at Balqhuidder (e.g.…”
Section: Introductionmentioning
confidence: 98%
“…Begun as a large collaborative project funded by the Environment Agency, Natural Environment Research Council, Forest Enterprise and the Forestry Commission reported in Neal and Reynolds 1998a, b, the work has been continued beyond the original timescale. It also complements research for streams in midWales (Neal et al, 2004a,b;Reynolds et al, 2004).…”
Section: Introductionmentioning
confidence: 99%